2020
DOI: 10.1038/s42003-020-0991-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite modulates aminoglycoside tolerance by inhibiting cytochrome heme-copper oxidase in bacteria

Abstract: As a bacteriostatic agent, nitrite has been used in food preservation for centuries. When used in combination with antibiotics, nitrite is reported to work either cooperatively or antagonistically. However, the mechanism underlying these effects remains largely unknown. Here we show that nitrite mediates tolerance to aminoglycosides in both Gram-negative and Gram-positive bacteria, but has little interaction with other types of antibiotics. Nitrite directly and mainly inhibits cytochrome heme-copper oxidases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The proteomic data show that the quantity of cyt bd is barely affected by the Fur loss. This concurs with the previous observations that there is no compensating production for cyt bd when cyt cbb 3 is depleted (Yin et al, 2016;Zhang et al, 2020). Nonetheless, activity of cyt bd is significantly impaired upon Fur inactivation, evidenced by increased susceptibility to nitrite (Fu et al, 2013;Meng et al, 2018b;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The proteomic data show that the quantity of cyt bd is barely affected by the Fur loss. This concurs with the previous observations that there is no compensating production for cyt bd when cyt cbb 3 is depleted (Yin et al, 2016;Zhang et al, 2020). Nonetheless, activity of cyt bd is significantly impaired upon Fur inactivation, evidenced by increased susceptibility to nitrite (Fu et al, 2013;Meng et al, 2018b;Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Further investigations into the NO-independent impacts of nitrite on HCOs have demonstrated that the essence of nitrite inhibition is proton translocation [153][154][155][156]. In P. aeruginosa, nitrite could not only prevent biofilm formation on the apical surface of airway epithelial cells but also modulate susceptibility to aminoglycosides by inhibiting bacterial respiration and oxygen uptake [157][158][159].…”
Section: Hcos Are Primary Targets Of Nitrite But Not No In Vivomentioning
confidence: 99%
“…[49] Additionally, the cyt aa 3 type of HCOs, such as ones from B. subtilis and S. aureus, were consistently found to be hypersensitive to nitrite. [47,50] Although cyt bd as hemoproteins are also susceptible to nitrite and NO revealed in early studies, [20] multiple lines of evidence support that HCOs are specific and most crucial targets of nitrite rather than of NO. Despite the hypersensitivity to nitrite, the S. oneidensis bd-deficient strain and the wild-type are indistinguishable from each other in their resistance to NO provided cyts c are produced at similar levels.…”
Section: Bacterial Targets Of Nitrite Revealed In Living Cellsmentioning
confidence: 99%
“…[51a] Indeed, in a variety of bacteria, including E. coli, P. aeruginosa, S. aureus, and B. subtilis, the NO-independent bacteriostasis of nitrite is attributable to inhibition of respiration. [50]…”
Section: Bacterial Targets Of Nitrite Revealed In Living Cellsmentioning
confidence: 99%
See 1 more Smart Citation